Near vision assessment for adults using the NIH Toolbox - Finley, John-Christopher A.; Slotkin, Jerry; Nowinski, Cindy J.; Bedjeti, Katy; Volpe, Nicholas; Weintraub, Sandra; Gershon, Richard (Frontiers in Neurology, 2025)
IntroductionThe National Institutes of Health (NIH) Toolbox Near Visual Acuity Test is a novel digitized measure designed to provide an assessment of near vision in a time-and cost-effective manner. This study is the first to report the psychometric properties of the NIH Toolbox Near Visual Acuity Test in a sample of community-dwelling middle-aged and older adults.MethodsNinety-eight adults (ages 40–81) completed the tablet-based near vision test and the gold standard chart-based near vision test. Performance on the tablet-and chart-based near vision tests was expressed in logarithmic units. Chart-and tablet-based administration order was counterbalanced. To assess test–retest reliability, the NIH Toolbox Near Visual Acuity Test was administered twice within the same day. Additionally, two equivalent versions of the chart-based test were randomly assigned to participants.ResultsAnalyses revealed that test–retest reliability of the NIH Toolbox Near Visual Acuity Test was good (intraclass correlation = 0.87, p < 0.001). Concurrence between the NIH Toolbox Near Visual Acuity Test and gold standard chart-based test was also good (r = 0.79, p < 0.001).DiscussionFindings provide support for the reliability and validity of the NIH Toolbox Near Visual Acuity Test as a near vision assessment for middle-aged to older adult populations. With further research, the integration of this test within the widely used NIH Toolbox may provide a more efficient means to understanding how near visual acuity influences neurocognitive test performance and brain function in middle-aged to older adult populations.